Why employees accept lower pay at mission-oriented companies - HUSSAIN, Insiya (Institutional Knowledge at Singapore Management University, 2023)
Today’s companies are likely to tout how their work benefits human welfare or “makes the world a better place.” Recent research suggests that this may come with a potential financial drawback for workers, as it can inhibit them from negotiating for higher pay. Over five studies, job candidates consistently reported that they worried asking for higher pay from these companies would be seen as greedy or inappropriate. This suggests they are aware of a common bias, known as motivation purity bias, where managers believe employees interested in material rewards of work (such as pay) are less motivated than those motivated by intrinsic rewards, such as the nature of the work. In reality, research has shown that extrinsic and intrinsic motivations operate jointly to predict high performance. Job candidates should invest in building their negotiation skills so they are less thrown off when companies use social impact framing. And organizations should train managers to be aware of the motivation purity bias.